An Unusual Variant of a Common Palatal Salivary Gland Tumor: Case Report of a Pleomorphic Adenoma with Significant Lipomatous Metaplasia - Sonal S. Shah; Tamer Zayed Moustafa (Case Reports in Dentistry)
Introduction. Salivary gland tumors are relatively common in the junction of the hard and soft palate area of the oral cavity. Pleomorphic adenoma is considered the most common benign salivary gland tumor in this location. Some of the rarer subtypes of this tumor may have a misleading clinical presentation. Recognition of these variants is important since long-standing pleomorphic adenomas have the potential to become malignant. Case Presentation. A healthy 24-year-old male was referred for a painless, large, slowly growing, exophytic swelling of the right hard and soft palate. Interestingly, the lesion was yellowish in color and soft to palpation, suggestive of an innocuous lipoma or cystic lesion. An incisional biopsy was performed and the diagnosis was consistent with pleomorphic adenoma with a significant adipose tissue component. The patient was referred to an oral surgeon and underwent a complete surgical excision. Upon two-year follow-up, the patient is doing well with no recurrences. Conclusion. This case highlights a rare microscopic variant of pleomorphic adenoma with altered clinical presentation that led to an erroneous clinical diagnosis. The importance of taking a biopsy for definitive diagnosis and appropriate management is reinforced.